Academic self‐efficacy in Bachelor‐level nursing students: Development and validation of a new instrument. (13th November 2019) - Bulfone, Giampiera; Vellone, Ercole; Maurici, Massimo; Macale, Loreana; Alvaro, Rosaria
Abstract: Aims: An available strategy to counteract academic failure is the development and implementation of student academic self‐efficacy; however, to date, there are no instruments measuring it. The aim of this study was to develop and psychometrically test an academic nurse self‐efficacy scale. Design: A longitudinal study design was used in accordance with Consensus‐based Standards for the Selection of health status Measurement Instruments guidelines. Methods: A convenience sample of 1, 129 nursing students attending the first year of the course were involved. The data collection began in 2014 and went on for 3 years. Data were collected at the beginning of the first (T0), at the end of the first (T1), at the end of the second (T2), and at the end of the third (T3) year. The academic nurse self‐efficacy scale was evaluated for content and face validity, for construct validity with explorative, confirmative factor analysis and hypothesis testing and for reliability. The standard error and the smallest detectable difference were also evaluated. Results: Scree plot analysis suggested a four‐factor solution and confirmative factor analysis model reached a good fit. We verified the first hypothesis, partially the second and not the third. The dimensions show a Cronbach's α 0.72–0.83. The smallest detectable difference was 26%. Conclusions: The academic nurse self‐efficacy scale had good validity and reliability and should be considered for nursing students. Impact: These findings may have an impact on universities, mainly in nursing degree programmes because nurse educators can identify nursing students with low academic self‐efficacy and help them in their academic duties. Indirectly, academic self‐efficacy monitoring can be used for evaluating the effect of different teaching strategies or mentorship support over time. Abstract : 目的: 学生学业自我效能的发展和实施是应对学业失败的有效策略; 然而, 到目前为止, 还没有测量它的仪器。本研究的目的是开发和心理测量的学术护士自我效能量表。 设计: 根据公认的健康状况测量仪器选择标准, 采用纵向研究设计。 方法: 以1129名护理学学生为研究对象, 采用便利抽样法对其进行调查。数据收集始于2014年, 持续了3年。数据收集始于第一年初(T0)、第一年末(T1)、第二年末(T2)和第三年末(T3)。对学术护理效能量表的内容效度、表面效度、构念效度进行探索性、验证性因素分析和假设检验, 并进行信度评估。并对标准误差和最小检测差异进行了评价。 结果: 碎石图分析提出了一个四因素解决方案, 验证因子分析模型达到了很好的拟合。我们验证了第一种假设, 第二种的部分, 而不是第三种。尺寸显示克伦巴赫α0.72 ‐ ‐0.83。最小的可检测到的差异为26%。 结论: 学术护士自我效能感量表具有良好的有效性和可信度, 值得护理专业学生参考。 影响: 这些发现可能会在大学产生影响, 主要是对护理学位项目上, 因为护理教育者能够发现学业自我效能低的护理学生, 并帮助他们完成学业任务。学业自我效能感监测可以间接地用于评估不同教学策略或辅导支持的效果。